Synthesis and Biological Evaluation of 2-Imino-Benzal-4-(2’Hydroxy Aryl)-Thiazoles and N-[-4’(2’’-Hydroxy Aryl)-Thiazoles]-4-Aryl-2-Azetidinones. - Milind Rahatgaonkar, Anjali (Asian Journal of Chemistry, 2010)
N-[4´(2"-hydroxy aryl)-thiazole]-4-aryl-2-azetidonones were prepared by the mechanism of cycloaddition reaction of acetyl chloride to ketenes in the presence of strong base triethylamine and neutral solvents as benzene.